Industrial training report: Perpustakaan Tengku Anis / Nik Azlina Ismail - Ismail, Nik Azlina (Perpustakaan Tengku Anis, 2024)
This paper contains report of activities that have been done by students while doing industrial training in Perpustakaan Tengku Anis (PTA) for the requirements of Industrial Training Report (IMC690) from 04 September 2023 until 31 January 2024. This course must be taken by final year students before their graduating on Bachelor of Information Science (Hons.) Library Management. This paper covers about background of library, services facilities, security and organizational structure. Besides, student have added every activity that has been carried out in every unit such as University Reference Unit or Cataloguing Unit, library services, University Archives Unit, Corporate and Collaboration Unit, Digital Library and lastly Administration and Strategic Unit. Then, the paper also added knowledge and skills, personal thoughts and opinion, lesson learnt, limitations and recommendations when undergoing industrial for 5 months. Last but not least, an appendices and description of the activities has been included in this paper.